(3JhLg GdbjGOGJ GdEOGQjI GdYQHjI aj Xd GdYhdeI (B:s (3OQGSI GSJWdGYjI JMSjSjI dYjfI ef GdeOjQjf aj GdbWGY GdeUQaj aj GdYQGb heUQ hGdLRGFQ hGdCQOf (B/s - (3Hf ejQI, BefI HhGTQi HfJs ((3GdEScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2005)
(3eONd fXQj YGe aj GdEOGQI GdYGedI ddYhdeI(B- (3NUGFU GdeOjQ GdYGdej(B- (3JhLgGJ GdbjGOGJ GdEOGQjI GdYQHjI GdYdjG aj Xd GdYhdeI(B- (3GdOQGSGJ GdSGHbI hefgLjI GdHMK GdejOGfj(B- (3YQV hJMdjd GSJLGHGJ CaQGO YjfI GdHMK(B- (3GNJHGQ aQVjGJ GdHMK hJMdjdgG(B- (3GdESJfJGLGJ hGdJhUjGJ(B.s
Keywords: (3GdYGde GdYQHjs; (3GdYhdeIs; (3GdbjGOIs; (3GdeUGQa(B- (3JfXje hEOGQIs